The quantum harmonic oscillator and catalan's constant. Issue 2 (October 2021) - Fassari, S.; Nieto, L.M.; Rinaldi, F.; San Millán, C.
Abstract : In this note we provide a representation of Catalan's constant in terms of a series involving the values at the origin of the even eigenfunctions of the quantum harmonic oscillator.